2023
DOI: 10.3389/fimmu.2023.1116224
|View full text |Cite
|
Sign up to set email alerts
|

Association between the systemic immune-inflammation index and kidney stone: A cross-sectional study of NHANES 2007-2018

Abstract: BackgroundThe incidence rate of kidney stones increased over the past decades globally, which brought medical expenditure and social burden. The systemic immune-inflammatory index (SII) was initially identified as a prognosis of multiple diseases. We performed an updated analysis on the impact of SII on kidney stones.MethodsThis compensatory cross-sectional study enrolled participants from the National Health and Nutrition Examination Survey 2007-2018. Univariate and multivariate logistic regression analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Di et al. reported that SII is positively connected with a high risk of kidney stones in U.S. adults under 50 years old ( 44 ). Furthermore, in patients with severe acute pancreatitis (SAP), Lu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Di et al. reported that SII is positively connected with a high risk of kidney stones in U.S. adults under 50 years old ( 44 ). Furthermore, in patients with severe acute pancreatitis (SAP), Lu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple covariates were obtained from interviews and examinations [ 16 ], including age, race (Mexican American, non-Hispanic Black, non-Hispanic White, other Hispanic, and other races), education level (less than 12th grade, high school graduate, and college graduate), family income-to-poverty ratio (<1.3, 1.3–3.5 and >3.5), marital status, body mass index (BMI, weight/height 2 , kg/m 2 ), smoking history, alcohol consumption history (<1 drink per week, 1–3 drinks per week, and >4 or more drinks per week), moderate recreational activity, vigorous recreational activity, DM, hypertension, and coronary heart disease. Moderate recreational activity was determined by the question “In a typical week do you do any moderate-intensity sports, fitness, or recreational activities that cause a small increase in breathing or heart rate such as brisk walking, bicycling, swimming, or golf for at least 10 min continuously?“.…”
Section: Methodsmentioning
confidence: 99%
“…The SII can be calculated through routine blood examination, which has the advantages of speed, efficiency, simplicity, and low cost. Previous studies have confirmed that the SII has good clinical value in diagnosing chronic diseases such as tumours, osteoporosis, kidney stones, and rheumatoid arthritis [ 12 15 ]. In addition, the SII is also considered to have good application value in predicting serum folate, albumin, vitamin B12, and vascular endothelial growth factor A (VEGF-A) concentrations [ 16 18 ].…”
Section: Introductionmentioning
confidence: 95%